INFRASTRUCTURES’ EFFECT ON ECONOMIC GROWTH IN SOUTHEAST SULAWESI - Manat Rahim; Armin Armin; La Ode Suriadi; Muh Armawaddin (Faculty of Economics and Business, University of Pasundan, 2019)
The aim of the research is to analyze the effect of infrastructures on economic growth in Southeast Sulawesi. The data used the secunder data which formed time series-based. The data was obtained by publication and legal documents of Statistic Center Unit and relevant institution. The method of analysis used ordinary least squares with panel data. Thus, the data analysis of this research was regretion model with panel data. To estimate regretion of panel data, the researcher used common effect,fixed effect and random effect method. The findings of this research showed that insfrastructures comprised road, harbor, water and electicity simultaniously and significantly influenced the economic growth in Southeast Sulawesi. Partially, only harbor and electricity significantly affected on the economic growth Southeast Sulawesi.